EFFECT OF FEEDING VARYING LEVELS OF PALM KERNEL CAKE ON PRODUCTION PERFORMANCE AND BLOOD METABOLITES OF LACTATING CROSSBRED DAIRY CATTLE - Z. Iqbal; M. A. Rashid; T. N. Pasha; J. A. Bhatti (Journal of Animal and Plant Sciences, 2019)
The objective was to evaluate the effects of increasing level of palm kernel cake (PKC) in concentrate feed on dry matter intake (DMI), body weight (BW), milk production,  milk composition and blood metabolites of dairy cows. Twenty one crossbred cows with average BW 410 ± 52.6 kg, producing 12 ± 3.2 kg of milk daily were blocked by their BW, previous lactation yield and days in milk (DIM). The animals were assigned to dietary treatments in a randomized complete block design (RCBD) with n=7 cows per treatment. Dietary treatments were: Control (C), PKC 20 and PKC 40 containing 0%, 20% and 40% PKC in concentrate diets, respectively. The duration of experiment was 70 days (d). Commonly used agro industrial by-products wheat bran and rice polishing were replaced with PKC. Body weight and body condition score (BCS) were measured at the start and then on a bi-weekly basis; whereas, feed intake and milk yield were recorded daily. Milk samples were collected twice a week (wk) and blood samples were taken weekly. Increasing level of PKC in concentrate diet had no effect (p>0.05) on DMI, fecal score, milk production and composition, BW and BCS gain as well as milk production efficiency. However, milk fat and total solids (TS) increased linearly (p<0.05) with increasing level of PKC. Plasma glucose, blood urea nitrogen (BUN) and non-esterified fatty acids (NEFA) concentrations were similar (p>0.05) among treatments. Inclusion of PKC at 40% increased milk fat and TS contents without affecting DMI, milk production, BW and BCS in crossbred dairy cows. It is concluded that PKC up to 40% can successfully replace wheat bran and rice polishing in dairy concentrate diet for crossbred cows.
Keywords: Palm kernel cake; Dairy cow; Milk production; Milk composition